Everything you wanted to know about the Korean language - Park, Dong-geun.; Kim, Jongho; Mouat, Colin; Kungnip Kugo?wo?n (Korea. (Seoul, Korea The National Institute of the Korean Language, 2010)
Provides overview of the Korean language, looking at pronunciation, grammar, linguistic history and so on. Suitable for self-study, building vocabulary, and developing reading, grammar and speaking skills.
Includes bibliographical references.
Elementary, Intermediate, and Advanced levels.
Keywords: Korean language; Korean language -- Study and teaching